THE IMPORTANCE OF INTERNET RESOURCES IN TEACHING VOCABULARY THROUGH COMMUNICATIVE LANGUAGE TEACHING - Sultonova Nargiza Utkirbek qizi (Journals Park Publishing, 2025)
This article investigates the effectiveness of using internet resources through CLT (Communicative Language Teaching) approaches for teaching vocabulary. Highlighting the crucial role of vocabulary acquisition in language learning, this study addresses the main difficulties students face during the process of learning a language and emphasize the methods. As the Internet technology is becoming common in the field of education, its support to learners’ is also significant. The given methodology in this article includes three important parts, such as preparation, accomplishment and evaluation. In this study we applied to qualitative approach including classroom observations and interviews by teacher in EFL setting and here it was used several internet resources such as e-dictionaries, websites and online videos. It can be visible from the results of our findings that these type of internet resources helped students in vocabulary acquisition by making it easier to learn, increase their motivation and communicative competence. The study gathers data on the usage of internet resources in CLT approaches which make the vocabulary acquisition easier, faster and more fascinating.
Keywords: Communicative Language Teaching, qualitative approach, internet resources, vocabulary acquisition, communicative competence, digital tools, feedback.